The Impact of Lean Production Pillars in Choosing Mass Customization Approaches: An Empirical Study - Aldabbagh, Tamadher (The Arab Journal of Administration, 2022)
The study aimed to know the nature of the relationship between the pillars of lean production in choosing mass customization approaches, which was applied in the Gulf craft Company in the United Arab Emirates. Reflective or process-oriented practices have paid special attention to knowing the impact of some of those pillars in choosing the approach most compatible and consistent with the nature of work in the organization. The primary data was collected from 100 respondents about the study variables from the field reality; the research relied on collecting the primary data for the study on the survey list to measure five selected pillars (timely production, manufacturing strategy, customer relations management, supplier relations management, and total quality management). The four international approaches to mass customization are (the collaborative approach, the adaptive approach, the cosmetic approach, and the transparent approach). The list contained the items of the research sample, and the list was designed to contain tools that can be used to measure the different variables of research. The research dealt with the procedures of statistical analysis and the methods that were used to achieve the objectives of the research, and the methods of statistical analysis that were followed by the analysis in both descriptive statistics, frequencies and percentages, weighted arithmetic averages, standard deviation, coefficient of variation, and arrangement in order to determine the characteristics of the research sample, analytical statistics using Statistical analysis software (SPSS v.20). The results showed that there is a statistically significant relationship between the pillars of Lean production and the choice of the mass customization approach. The results also indicate that the independent variable (some of the pillars of Lean production) had a significant effect on the dependent variable (the transparent approach to mass customization).